THE ROLE OF THE CURRENT SCHOOL EDUCATION SYSTEM IN EDUCATING INDIA - Choudhary, Anu; Yadav, Suresh Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
India's school education system has undergone significant transformations over the past two decades, aiming to address the diverse needs of its vast population. With initiatives like the Right to Education Act (RTE) of 2009, the Sarva Shiksha Abhiyan (SSA), and the National Education Policy (NEP) 2020, the country has made strides toward universalizing education and improving its quality. However, challenges persist, including disparities in access, quality, and infrastructure.